Penerapan Metode MDLC dengan Adobe Animate Untuk Media Pembelajaran Interaktif Mata Pelajaran Ilmu Pengetahuan Sosial di Sekolah Menengah Pertama - tri hartanti, ninik (Jurnal Nasional Teknologi Komputer, 2024)
Technological developments in Indonesia, especially in the field of education, are increasing. After adjustments to the implementation of the education curriculum due to Covid-19, a lot of software was created to support the education system in Indonesia, such as the Zoom application, Google Meet, and others. All of these video conferencing applications trigger new learning methods for all levels of education from elementary to university. One of them is the interactive learning media model provided at the school education level. This interactive learning media is applied using a smartphone so that it can function as a teaching aid in learning activities. Through interactive learning media, teaching materials in schools will be discussed, especially social sciences (IPS). The existence of interactive learning tools will be able to adapt to the needs of teaching and learning activities. This research aims to design learning applications by applying a design method which consists of six steps including concept, design, material collection, manufacture, testing and distribution. Creating interactive learning tool models using several software, namely Adobe Animate and Adobe Illustrator, as well as several other supporting applications. Through this interactive learning media, there is a main menu which contains material, competency standards, quizzes and applications.